Injuries in children and adolescents - Soetjiningsih Soetjiningsih (Paediatrica Indonesiana, 1999)
Morbidity and mortality caused by injuries in children increasing from year to year. The objective of this study was to investigate the incidence of injuries among children and adolescents who required inpatient or outpatient care in the Emergency Unit Sanglah Hospital. This study was carried out by using restrospective method, by taking the data from the medical records of children under 18-yr-old who required inpatient or outpatient care caused by injuries, at the Emergency Unit Sanglah Hospital, during the period of January 1 - December 31 , 1996. The data were presented descriptively in the form of table, classified based on age, sex, and type of injuries. Statistically analysed by using chi-square test, it was considered significance if p<0.05. During the 1996 period, it was found 4,801 injuries on children, averagely 400 injuries per month. The highest number of incidence found in children aged 13-18 years (45%), boys were 3 times higher than girls, mostly (75.8%) due to the traffic injuries and 24.2% domestic injuries. The highest number of domestic injuries was found in children aged 1-5 years (57.5%) and the most frequent cause of domestic injuries was due to falling down, foreign bodies, animal bites, and bum. lt was really needed an injury control in a wider scope.